Nitric oxide mediates apoptosis and mitochondrial dysfunction and plays a role in growth hormone deficiency by nivalenol in GH3 cells. Issue 1 (December 2017) - Huang, Deyu; Cui, Luqing; Guo, Pu; Xue, Xijuan; Wu, Qinghua; Hussain, Hafiz; Wang, Xu; Yuan, Zonghui
Abstract Nivalenol (NIV), a type B trichothecenes commonly found in cereal crops, can cause growth impairment in animals. However, limited information about its mechanisms is available. Trichothecenes have been characterized as an inhibitor of protein synthesis and induce apoptosis in cells. Oxidative stress is considered an underlying mechanism. However, whether NIV can induce oxidative stress and apoptosis in rat pituitary cells line GH3 is unclear. The present study showed that NIV significantly reduced the viability of cells and caused oxidative stress in GH3 cells. Further experiments showed that nitric oxide (NO), but not ROS, mediated NIV-induced oxidative stress. Additionally, NIV induced caspase-dependent apoptosis, decrease in mitochondrial membrane potential and mitochondrial ultrastructural changes. However, NIV-induced caspase activation, mitochondrial damage and apoptosis were partially alleviated by Z-VAD-FMK or NO scavenger hemoglobin. Finally, NIV changed the expression of growth-associated genes and pro-inflammatory cytokines. NIV also reduced the GH secretion in GH3 cells, which was reversed by hemoglobin. Taken together, these results suggested that NIV induced apoptosis in caspase-dependent mitochondrial pathway in GH3 cells, which might be an underlying mechanism of NIV-induced GH deficiency. Importantly, NO played a critical role in the induction of oxidative stress, apoptosis and GH deficiency in NIV-treated GH3 cells.